1960
DOI: 10.1002/j.1537-2197.1960.tb07175.x
|View full text |Cite
|
Sign up to set email alerts
|

A Cytogenetic Study of Clarkia Unguiculata Ii. Supernumerary Chromosomes

Abstract: Mooring, John S. (Washington State U., Pullman.) A cytogenetic study of Clarkia unguiculata. II. Supernumerary chromosomes. Amer. Jour. Bot. 47(10): 847–854. Illus. 1960.—Supernumerary chromosomes morphologically comparable to those of the basic complement occur in high frequency in wild populations of this onagraceous annual plant. This paper evaluates the role that these supernumerary chromosomes play in the population dynamics of this species. The results of crossing plants with various numbers of supernume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1961
1961
1980
1980

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 22 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…The overall frequency of individuals with one or more extra chromosomes is 8.8% which compares reasonably closely with the figure of 10.6% for the Eriophyllum lanatum complex (Mooring, 1975). Their relative frequency in Chaenactis diploids and polyploids is the opposite of that known, as is the case in most other species Ehrendorfer (1959) and Mooring (1960) havr suggested possible explanations for their fre quency in populations of Achillea and Clarkia respectively, and the studies summarized bJ Battaglia (1964), Darlington (1963) and Steb bins (1971) have shown that they should no be summarily dismissed as sporadic aberra tions.…”
Section: Discussion-extra Chromosomes-that Individuals With Extra Chrmentioning
confidence: 95%
See 1 more Smart Citation
“…The overall frequency of individuals with one or more extra chromosomes is 8.8% which compares reasonably closely with the figure of 10.6% for the Eriophyllum lanatum complex (Mooring, 1975). Their relative frequency in Chaenactis diploids and polyploids is the opposite of that known, as is the case in most other species Ehrendorfer (1959) and Mooring (1960) havr suggested possible explanations for their fre quency in populations of Achillea and Clarkia respectively, and the studies summarized bJ Battaglia (1964), Darlington (1963) and Steb bins (1971) have shown that they should no be summarily dismissed as sporadic aberra tions.…”
Section: Discussion-extra Chromosomes-that Individuals With Extra Chrmentioning
confidence: 95%
“…Alternatively, it may be that polyploids here can tolerate extra chromosomes more easily than can diploids. It seems likely, however, that the comparatively high frequency of extra chromosomes at all ploidy levels may reflect the presence of some mechanism that increases their number, as in Clarkia unguiculata(Mooring, 1960) and a number of other species. Unlike the situation in Eriophyllum lanatum, however, individuals with extra chromosomes do not seem to be overrepresented in some regions or in plants derived from seed sown in the greenhouse.…”
mentioning
confidence: 99%